Manajemen Beban Kerja dan Stres Kerja: Pengaruhnya terhadap Kinerja Karyawan Bagian Produksi di PT X - Salsabila, Anida; Mulyana, Aam Rachmat (Universitas Batanghari, 2024)
This research aims to explore various aspects of the phenomenon. of workload and job-related stress impacting the performance of production employees at company X is examined. The research, conducted using a quantitative method and multiple analysis techniques, involved 63 production employees as respondents. The partial research results indicate that workload Detrimentally impacts employee performance, whereas work stress Does not produce a notable influence. This suggests that increasing workload negatively impacts employee performance. Ultimately, This study emphasizes the importance of taking into account the influence of workload on employee performance, As it plays a critical role in determining whether a company succeeds or fails.